2022
DOI: 10.3390/cells12010044
|View full text |Cite
|
Sign up to set email alerts
|

Association between Immunosenescence, Mitochondrial Dysfunction and Frailty Syndrome in Older Adults

Abstract: Aging is associated with changes in the immune system, increased inflammation and mitochondrial dysfunction. The relationship between these phenomena and the clinical phenotype of frailty is unclear. Here, we evaluated the immune phenotypes, T cell functions and mitochondrial functions of immune cells in frail and robust older subjects. We enrolled 20 frail subjects age- and gender-matched with 20 robust controls, and T cell phenotype, response to immune stimulation, cytokine production and immune cell mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Ilaria Buondonno et al. also reported decreased numbers of CD4+ and CD8+ T cells in frail subjects, while CD4+/CD8+, memory, and naive T cells were unaffected by frailty [ 51 ]. Interestingly, Gilda Varricchi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ilaria Buondonno et al. also reported decreased numbers of CD4+ and CD8+ T cells in frail subjects, while CD4+/CD8+, memory, and naive T cells were unaffected by frailty [ 51 ]. Interestingly, Gilda Varricchi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, frail people present an immune profile more senescent than robust people with a higher rate of terminally differentiated CD8 + CD28-T cells [ 28 , 29 ] and a lower IL-17 production after in vitro stimulation [ 29 ].…”
Section: The Impact Of Physiological Aging Focus On Immunosenescencementioning
confidence: 99%
“…The flu vaccination is undoubtedly that which has been studied and known for the longest time; it is known that when carried out annually, it is able to reduce complications, hospitalizations, and deaths due to this infection [ 28 , 29 ]. Although vaccine effectiveness may be lower in older adults than younger individuals due to age-related changes in the immune system, getting vaccinated can still provide significant benefits, reducing the risk of serious disease in less compromised older adults and minimizing the annual risk of frailty [ 30 , 31 ]. A meta-analysis showed that the flu vaccine was capable of inducing effective immunization in 51% of individuals up to 65 years of age and only 43% of people over 65 years of age [ 32 ].…”
Section: Efficacy Of Vaccines In the Elderlymentioning
confidence: 99%